Enhancing Students’ Understanding of Islamic History through Jigsaw Cooperative Learning in SKI at MIS Bilingual Al-Islam Sukomoro - M. Isa Idris Su’udi; Mahmudi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve the understanding of Islamic History (SKI) among students at MIS Bilingual Al-Islam Sukomoro through the application of Jigsaw Cooperative Learning. The study focuses on utilizing the Jigsaw method to enhance student engagement and learning outcomes in Islamic History subjects. The Jigsaw method, which emphasizes group collaboration and peer teaching, is believed to foster a deeper understanding of the material, increase student participation, and improve critical thinking skills. The research was conducted in two cycles, involving students from the 7th grade of MIS Bilingual Al-Islam Sukomoro. In each cycle, students were divided into small groups, with each group responsible for mastering different sections of the SKI material. Afterward, students came together in a "home" group to share and teach the content they had learned, ensuring comprehensive understanding among all members. Data was collected through observations, interviews, and tests, and the results showed significant improvement in both student engagement and academic achievement in the SKI subject. The findings indicate that the Jigsaw method not only improved students’ understanding of Islamic History but also enhanced their social and communication skills, fostering a positive and collaborative classroom environment. Additionally, students exhibited a greater sense of responsibility for their own learning as well as for the success of their peers. This study highlights the potential of the Jigsaw method in fostering cooperative learning and enhancing subject comprehension. It suggests that teachers of SKI and similar subjects in bilingual schools can benefit from incorporating this strategy to achieve better learning outcomes.